TINJAUAN YURIDIS PENGEMBANGAN PERKEBUNAN KELAPA SAWIT BERDASARKAN UUPA DI TANAH MERAH PAPUA - Adik Sukmawati (jurnal.unprimdn.ac.id, 2022)
In light of the government's policy of issuing permits for land clearing for oil palm plantations with the aim of increasing the area of oil palm plantations in Papua from 6 million to 20 million hectares based on Law Number 18 of 2004 concerning Plantations and TAP MPR Number IX /MPR/2001 concerning Agrarian Reform and Natural Resource Processing. Law No. 32 of 2004 established the independence of the provincial and district governments. The purpose of this study is to raise, examine, and critically assess the legal analysis of the construction of an oil palm plantation based on the LOGA in Tanah Merah Papua. Therefore, qualitative research methodology and normative juridical are needed, which use analytical techniques in the form of library research. The findings of this study indicate that clearing forests for oil palm plantations will exacerbate the impacts of climate change and ultimately damage the environment. The environment will be more vulnerable to pests, diseases, erosion processes, and land degradation due to loss of biodiversity.